2017
DOI: 10.1155/2017/2562957
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Imaging Parameters of the Paraspinal Muscles, Spinal Degeneration, and Low Back Pain

Abstract: This narrative review investigated imaging parameters of the paraspinal muscles and their association with spinal degenerative features and low back pain (LBP) found in the literature. Three principal signs of muscle degeneration were detected on imaging: decreased muscle size, decreased radiographic density, and increased fat deposits. Men have a higher density of paraspinal muscles than women, younger individuals have a higher density than older ones, and lean individuals have a higher density than those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
198
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(234 citation statements)
references
References 65 publications
23
198
2
11
Order By: Relevance
“…Interestingly, our results also showed PS muscles had high percentages of FAPs of which were more adipogenic and had greater cell proliferation rates compared to the hindlimb muscles. Clinically, PS muscles are known to develop FI in a number of spine conditions such as degenerative disc disease and scoliosis . Most studies of PS FI center on imaging quantification of FI and correlation to clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our results also showed PS muscles had high percentages of FAPs of which were more adipogenic and had greater cell proliferation rates compared to the hindlimb muscles. Clinically, PS muscles are known to develop FI in a number of spine conditions such as degenerative disc disease and scoliosis . Most studies of PS FI center on imaging quantification of FI and correlation to clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although FI is common in RC tears, this pattern of pathology is not ubiquitous across all types of musculotendinous injuries at all anatomic locations, with the exception of some genetic condition, such as muscular dystrophies, and more global metabolic disturbances such as obesity and type 2 diabetes . Multiple studies have observed high degrees of FI in paraspinal muscles in patients with congenital and degenerative spine diseases . Conversely, the development of intramuscular fibrosis rather than FI appears to be the hallmark of volumetric muscle injuries that involve the extremities .…”
mentioning
confidence: 99%
“…Changes to the MF apparent with MRI imaging are strongly associated with back pain, but the diagnostic value in individual patients of such changes is limited, since back pain of any cause can lead to changes of the MF cross sectional area and amount of fat infiltration (79). Prolonged bed rest in the absence of back pain can also lead to atrophy of the MF seen on imaging (80) and the atrophy can be reversed with appropriate exercises (81).…”
Section: Imaging Assessment Of Motor Control Dysfunctionmentioning
confidence: 99%
“…There is limited literature assessing paraspinal muscle atrophy with regard to thoracolumbar pathology. Kalichman et al 8 suggest an association between paraspinal muscle atrophy and spondylolisthesis, facet joint osteoarthropathy, and disc space narrowing. A study composed of patients with moderate (ODI < 42) and severe (ODI !…”
Section: The Role Of Paraspinal Muscle Atrophy In Thoracolumbar Pathomentioning
confidence: 99%